Concise total synthesis of (±)-pileamartines A and B. Issue 24 (15th November 2022) - Xu, Wei; Wang, Taimin; Zhou, Xin; Fang, Lijing; Zhang, Chen; Zhai, Hongbin; Cheng, Bin
Abstract : A concise total synthesis of (±)-pileamartines A and B, a pair of alkaloids sharing an unprecedented tetracyclic skeleton, was achieved in 9 and 8 linear steps, respectively. Abstract : A concise total synthesis of (±)-pileamartines A and B, a pair of alkaloids sharing an unprecedented tetracyclic skeleton, was achieved in 9 and 8 linear steps, respectively. The key steps include an NHC-catalyzed tandem aza-benzoin/Michael reaction to rapidly establish the polyhydroindenopyrrole core, a diastereoselective reductive allylation of pyrrolidone, and an RCM to construct the piperidine ring.